A little information goes a long way: Expertise and identity theft. (January 2015) - Vieraitis, Lynne M.; Copes, Heith; Powell, Zachary A.; Pike, Ashley
Abstract: Experts have a way of seeing the world in ways that differ from novices. Research on offenders suggests that as they develop expertise in their chosen crimes they become better skilled at recognizing opportunities and evading detection. The bulk of research emphasizes the role of criminal experience on offenders' abilities to quickly assess situations and commit crimes at that moment but little has been done to examine how expertise influences crimes that cannot be committed on the spot. Our aim is to examine the importance of expertise on the commission of identity theft (a crime that requires time to commit). We highlight the roles of both legitimate and illegitimate experiences in developing skills to be successful. In addition, we show how expertise not only effects criminał event decisions but criminal involvement decisions (specifically persistence).